Ответы и объяснения

Лучший Ответ!
2013-10-28T15:11:35+00:00
Б)   \frac{6 x^{2} -3x-3}{ x^{2} +x-6} =1+ \frac{4x}{x+3};
x \neq -3;x \neq 2.
 \frac{6 x^{2} -3x-3}{ (x+3)(x-2)} = \frac{5x+3}{x+3}; умножим на (x+3)(x-2)
6 x^{2} -3x-3=5 x^{2} -7x-6;
x^{2} +4x+3=0;D=1; x=-1;x=-3 посторонний корень
Ответ  x=-1
3)   \frac{2x+1}{( x^{2} +1)(x+2)}= \frac{A}{x+2}+ \frac{Bx+C}{ x^{2} +1};
 \frac{2x+1}{( x^{2} +1)(x+2)}=  \frac{A(x^{2} +1)+(Bx+C)(x+2)}{ (x+2)(x^{2} +1)};
2x+1=A x^{2} +B x^{2} +Cx+2Bx+A+2C;
2x+1=(A+B) x^{2} +(C+2B)x+(A+2C);
A+B=0;C+2B=2;A+2C=1;
A=-0,6;B=0,6;C=0,8;